Factors Preventing Widespread Vaccine Uptake among Adults - Alissa V. Katsaras; Kathryn A. Stofer; Helen Yates; LaToya J. O'Neal (EDIS)
This publication is part of the Adult Vaccination in Florida series. This document explores the prevailing factors preventing widespread vaccine uptake by adults in the United States and outlines the most relevant trends and patterns that are seen in direct connection to vaccine uptake among adults. Written by Alissa V. Katsaras, Kathryn A. Stofer, Helen Yates, and LaToya J. O’Neal, and published by the UF/IFAS Department of Agricultural Education and Communication, October 2024.